2020
DOI: 10.1109/jphot.2020.3039988
|View full text |Cite
|
Sign up to set email alerts
|

A Single-Mode Erbium Fiber Laser With Flat Power Output and Wide Wavelength Tunability

Abstract: In this research, we present and study an erbium fiber laser with triplefiber-ring (TFR) scheme for continuous-wave (CW) wavelength-selection. The designed TFR not only can achieve single-longitudinal-mode (SLM) oscillation, but also can spread the tuning range from 1519.0 to 1583.0 nm covering C-and part of L-bands. Moreover, 0 dB power fluctuation can be obtained from 1523.0 nm to 1559.0 nm for flattened operation based on the compound-ring configuration. The Lorentzian laser linewidths of 22 to 29 kHz are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…In addition, according to the well-versed Schawlow-Townes formula [3], ring laser with a longer cavity length has a longer photon lifetime, in which narrower linewidth is easier to obtain [4]. Therefore, numerous approaches have been proposed to achieve single-longitudinal-mode oscillation from fiber ring laser, such as employing a phase-shifted fiber Bragg grating (FBG) to form an ultra-narrow filter [5], utilizing an unpumped Er 3+ -doped fiber as a saturable absorber [6], adopting a compound-ring cavity structure based on Vernier effect [7], and the combination of two or even more of these schemes [8]. Nevertheless, for fiber ring laser, cavity length cannot be increased indefinitely.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, according to the well-versed Schawlow-Townes formula [3], ring laser with a longer cavity length has a longer photon lifetime, in which narrower linewidth is easier to obtain [4]. Therefore, numerous approaches have been proposed to achieve single-longitudinal-mode oscillation from fiber ring laser, such as employing a phase-shifted fiber Bragg grating (FBG) to form an ultra-narrow filter [5], utilizing an unpumped Er 3+ -doped fiber as a saturable absorber [6], adopting a compound-ring cavity structure based on Vernier effect [7], and the combination of two or even more of these schemes [8]. Nevertheless, for fiber ring laser, cavity length cannot be increased indefinitely.…”
Section: Introductionmentioning
confidence: 99%
“…In the same year, Wang et al [19] of Beijing University of Posts and Telecommunication proposed a SLM fiber laser based on a convex-shaped fiber ring combined with a fiber grating and an unpumped erbium-doped fiber loop, and a laser linewidth of 840 Hz and a laser output of 9.21 mW were realized. In 2020, Yeh et al [20] presented a tunable single-frequency narrow linewidth fiber laser with erbium doped fiber (EDF) as SA and self-feedback injection and the wavelength tuning range was 60 nm with an average output linewidth of 18 kHz. In 2022, Wan et al [21] of Shanghai University reported a ring-cavity single-frequency fiber laser with Bi/Er/Yb co-doped fiber as the SA, and the tested linewidth was less than 7.5 kHz.…”
Section: Introductionmentioning
confidence: 99%
“…However, the EDF ring lasers with stable single-longitudinal-mode (SLM) operation will be hard to accomplish principally because of the long fiber cavity and the dense multi-longitudinal-mode (MLM) oscillation induced by the homogenous broadening effect of EDF [6], [7]. To ensure and reach the SLM action in the EDF ring fiber laser with advantageous output performance, numerous methods have been operated in the fiber ring cavity, such as using the Mach-Zehnder interferometer (MZI) scheme [8], saturable absorber (SA) based filter [9], [10], Rayleigh backscattering (RB) injection [11], compound fiber ring configuration [12], [13], and narrower optical filter [14], [15]. Chien-Hung Yeh, Li-Hung Liu, Han-Shin Ko, and Yi-Ting Lai are with the Department of Photonics, Feng Chia University, Taichung 407802, Taiwan (e-mail: yeh1974@gmail.com; jk1992581@gmail.com; xzbc699@gmail.com; laietn@gmail.com).…”
Section: Introductionmentioning
confidence: 99%